Encouraging indigenous knowledge production for Wikipedia. Issue 3 (3rd July 2021) - Kristiani, Ivonne
ABSTRACT: Digital technology has transformed the way knowledge is produced, mediated and accessed. Wikipedia, as by far the most visited and significant source of information on the Internet, plays a crucial role in shaping the information people read. Even though its vision is to record the "sum of all human knowledge", there are still significant imbalances in representation between Western knowledge traditions and indigenous knowledges in the global South on Wikipedia. Drawing upon experiences from indigenous knowledge documentation projects in Indonesia as case studies, this paper explores the challenges of incorporating indigenous knowledge to Wikipedia and proposes some suggestions to achieve knowledge equity.